2002
DOI: 10.1046/j.1365-2672.2002.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-contamination of carcasses and equipment during pork processing

Abstract: Aims:The cross-contamination events within a commercial pork processing line were examined by a combination of ERIC-PCR DNA fingerprinting of Escherichia coli and plate counts. Methods and Results: Sponge sampling of environmental surfaces and carcasses was performed over an 8-h processing period. Prior to the start of processing the scraper and dry polisher blades were found to harbour substantial Enterobacteriaceae and Escherichia coli populations. From plate count data the key cross-contamination site for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
8
23
1
1
Order By: Relevance
“…Contaminated equipment, are generally recognised as major sources of cross-contaminations in meat processing units (Small & Buncic, 2009;Warriner et al, 2002). Nevertheless, the risk of Salmonella occurrence was found to be significantly reduced within retail establishments, whose personnel were trained in hygienic meat handling practices.…”
Section: Risk Factors For Salmonella Contamination In the Retailed Meatmentioning
confidence: 99%
“…Contaminated equipment, are generally recognised as major sources of cross-contaminations in meat processing units (Small & Buncic, 2009;Warriner et al, 2002). Nevertheless, the risk of Salmonella occurrence was found to be significantly reduced within retail establishments, whose personnel were trained in hygienic meat handling practices.…”
Section: Risk Factors For Salmonella Contamination In the Retailed Meatmentioning
confidence: 99%
“…Fraser and Monteiro (2009) identify abattoirs as the bottleneck of the food supply chain, and as products from different producers are consolidated, there is an increased risk of cross-contamination (Kö ppel et al, 2009). Warriner, Kaur, and Dodd (2002) and Galland (1997) suggest that there are many opportunities for contamination during meat processing; however, the most likely stage for contamination is during slaughter at the end of the evisceration. They therefore assert that there is a particular need to develop a HACCP to minimise the risk of cross-contamination at this stage of the process.…”
Section: Contaminationmentioning
confidence: 99%
“…In a study conducted in 4 European countries, Hald et al (2003) reported that 9.4% of 384 carcass splitter machines were contaminated with Salmonella during the slaughtering process. In addition, Warriner et al (2002) demonstrated that E. coli and potential enteric pathogens can be transferred between pork carcasses through the splitting saw. Therefore, cleaning and disinfection of the splitting saw should be carried out after splitting each carcass in order to reduce the risk of cross contaminations.…”
Section: Carcass Splittingmentioning
confidence: 99%